Inhibitory Control pada Anak dengan Perkembangan Tipikal: Systematic Literature Review - Zefanya Oslowahadestizia Manik; Enjang Wahyuningrum; Margaretta Erna Setianingrum (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study aims to review empirical research on inhibitory control in typically developing children aged 3-7 years. A Systematic Literature Review (SLR) was conducted using PRISMA guidelines to analyze articles published between 2021 and 2026. The findings show that inhibitory control develops rapidly during early childhood and is influenced by factors such as structured physical activities, rule-based play, parenting practices, socioeconomic status, and nutrition. Several interventions, including motor activities, gymnastics, music play, and language-based play, were found to improve inhibitory control. In addition, inhibitory control is associated with school readiness, academic achievement, and socio-emotional development. In conclusion, inhibitory control can be strengthened through structured learning experiences in early childhood, highlighting the importance of supportive educational and environmental contexts.